Exploring β-glucosidase activity in lactic acid bacteria isolated from natural and alkaline-treated Turkish table olives: a molecular and biochemical approach - Mumcu, Ayla; Altuntas, Evrim Gunes; Sozbilen, Gozde Seval; Gungor, Feriste Ozturk; Sevim, Busra; Deliboran, Aise; Cetin, Oznur; Eray, Oguzhan; Ergun, Burcu Gunduz (SPRINGER, 2025)
This study aims to identify and characterize lactic acid bacteria strains (LAB) with high debittering activity from Turkish table olives, focusing on beta-glucosidase activity and oleuropein degradation. A total of 353 LAB isolates were obtained from the different fermentation stages of natural and alkaline-treated olives, and screened for beta-glucosidase activity through API ZYM system, while oleuropein tolerance and degradation were determined by HPLC. Of the 25 isolates exhibiting high beta-glucosidase activity, 21 were identified as Lactiplantibacillus plantarum and 2 as Lactiplantibacillus pentosus based on 16 S rDNA sequencing. beta-glucosidase production was investigated at the gene level by determining the presence of the bglH3 gene. PCR analysis revealed the presence of the bglH3 gene in 10 isolates. All strains tolerated and grew in oleuropein-containing media in parallel with the presence of enzymes, indicating their ability to metabolize this bitter compound. These findings suggest that certain Lactiplantibacillus strains from Turkish table olives possess enzyme activity that plays an important role in improving the debittering during fermentation, with variability in their debittering levels among different strains. Using strains with high beta-glucosidase activity as starter cultures in table olive production enhances debittering efficiency, shortens fermentation periods, accelerates production, and boosts yield, while reducing labor and storage costs. Furthermore, selecting appropriate starter cultures provide a natural, safe, and eco-friendly alternative to chemical treatments like lye (NaOH), which can be costly and environmentally harmful. This approach promotes cost-effective, sustainable, and consumer-preferred olive production, delivering both ecological and economic advantages to producers and the food industry.
Keywords: Lactic acid bacteria; Fermentation; Beta-glucosidase; Lp. plantarum; Table olive; Oleuropein; LACTOBACILLUS-PLANTARUM STRAINS; OLEUROPEIN HYDROLYSIS; IN-VITRO; SPANISH; GENE; IDENTIFICATION; DEGRADATION; MICROBIOTA; SELECTION; Food Science & Technology